Negotiation theories and concepts - Haslinda Abdullah (UPNM Press, Universiti Pertahanan Nasional Malaysia, 2016)
Negotiation: theories and concepts is for students and professionals and anyone whose aim is to gain knowledge and skills in negotiating effectively using the techniques and strategies explained in a simplified manner in this book.